Reputation and multiple stakeholder outcomes: The role of organizational culture and customer trust - Nasser, Hasan; Beydoun, Abdulrahman; Ali, AlaaEldin Abbass (Edelweiss Applied Science and Technology, 2025)
In the current landscape, characterized by significant volatility, organizations are increasingly focused on grasping and harnessing the perceptions of their varied stakeholders to establish an enduring competitive edge. As such, organizational culture, business reputation, and customer trust are vitally important concepts for practitioners and academicians because of their possible influence on external and internal stakeholders. Given the amplified importance of the multi-stakeholder standpoint, this study engages in path analysis using SPSS-AMOS software to examine the mediating influence of perceived company reputation between organizational culture and customer trust on one side and employee engagement and customer satisfaction on the other side among 135 Lebanese hotel visitors and 189 Lebanese hotel staff through a questionnaire survey using a convenience sampling technique. The results acknowledge the influence of culture and consumer trust on reputation and multiple stakeholder outcomes. Additionally, reputation influences customer satisfaction but not employee engagement. Finally, reputation partially mediates the connection between trust and satisfaction but does not mediate the relationship between culture and employee engagement. This study can contribute to the Lebanese hotels’ management efforts in improving hotels’ reputation and satisfying customers through positive organizational culture and customer trust.